Distribution of chemical elements in an old metallurgic area, Zenica (Central Bosnia) - Alijagić, Jasminka (2008)
The objective of this work is the study of the distribution of chemical elements in topsoil and bottom soil for the identification of anthropogenic (man-made) and geogenic (natural) element sources in an old metallurgic area on a local scale. At 62 different sites, samples of attic dust, topsoil (0-5 cm depth) and bottom soil (20-30 cm depth) have collected in 52 km2 of the Zenica area. Analysis for 42 chemical elements has performed. Based on a comparison of statistical parameters, spatial distribution of particular elements and results of cluster and factor analysis, two natural and one anthropogenic geochemical associations were identified.